2022
DOI: 10.1002/adom.202200099
|View full text |Cite
|
Sign up to set email alerts
|

Broad‐Band Visible‐Light Excitable Room‐Temperature Phosphorescence Via Polymer Site‐Isolated Dye Aggregates

Abstract: Organic room‐temperature phosphorescent (RTP) materials are useful in optical imaging and sensing technologies. However, most organic phosphors, including red‐light emitting dyes, exhibit unusually large Stokes shifts, and require excitation with ultraviolet radiation, the high energy of which can induce substantial photo damage. Here a design concept of using dihydroxy‐functionalized naphthalenediimide (NDI, λabs < 400 nm) is demonstrated to initiate ring‐opening polymerizations of L‐lactide (PLA) and ε‐capro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…[28b] When the BF 2 dbm is modified with a single atom, however, a more significant RTP shift in emission maximum (525 to 535 nm, 356 cm À 1 ) is obtained for BF 2 dbm(I) aggregates, [28a] presumably due to a mixed singlet transition dipole moment. Very recently, we also demonstrated that the formation of dibromo-substituted naphthalenediimide (NDI) aggregates leads to red-shifted RTP emission maximum vs. the monomer RTP (670 to 700 nm, 639 cm À 1 ) while the unsubstituted NDI aggregates have negligible spectral changes; [29] nonetheless, the shift is mostly due to re-distributed vibronic populations while the position of the 0-0 transition does not change much. Incidentally, to show that the mixing of singlet excited state into the triplet one could promote phosphorescence spectral shift for TPA aggregates (Figure 3), we compared the phosphorescence spectra of the TPA with three internal heavy atoms, tris(4bromophenyl)amine (TPA-3Br), at a concentration of 0.5 wt % and 12 wt % in PS at 80 K, respectively, and indeed observed a change in emission maximum from 433 to 455 nm, or 1117 cm À 1 in energy (Figure 3b).…”
Section: Methodsmentioning
confidence: 97%
“…[28b] When the BF 2 dbm is modified with a single atom, however, a more significant RTP shift in emission maximum (525 to 535 nm, 356 cm À 1 ) is obtained for BF 2 dbm(I) aggregates, [28a] presumably due to a mixed singlet transition dipole moment. Very recently, we also demonstrated that the formation of dibromo-substituted naphthalenediimide (NDI) aggregates leads to red-shifted RTP emission maximum vs. the monomer RTP (670 to 700 nm, 639 cm À 1 ) while the unsubstituted NDI aggregates have negligible spectral changes; [29] nonetheless, the shift is mostly due to re-distributed vibronic populations while the position of the 0-0 transition does not change much. Incidentally, to show that the mixing of singlet excited state into the triplet one could promote phosphorescence spectral shift for TPA aggregates (Figure 3), we compared the phosphorescence spectra of the TPA with three internal heavy atoms, tris(4bromophenyl)amine (TPA-3Br), at a concentration of 0.5 wt % and 12 wt % in PS at 80 K, respectively, and indeed observed a change in emission maximum from 433 to 455 nm, or 1117 cm À 1 in energy (Figure 3b).…”
Section: Methodsmentioning
confidence: 97%
“…[28b] When the BF 2 dbm is modified with a single iodine atom, however, a more significant RTP shift in emission maximum (525 to 535 nm, 356 cm À 1 ) is obtained for BF 2 dbm(I) aggregates, [28a] presumably due to a mixed singlet transition dipole moment. Very recently, we also demonstrated that the formation of dibromo-substituted naphthalenediimide (NDI) aggregates leads to red-shifted RTP emission maximum vs. the monomer RTP (670 to 700 nm, 639 cm À 1 ) while the unsubstituted NDI aggregates have negligible spectral changes; [29] nonetheless, the shift is mostly due to re-distributed vibronic populations while the position of the 0-0 transition does not change much. Incidentally, to show that the mixing of singlet excited state into the triplet one could promote phosphorescence spectral shift for TPA aggregates (Figure 3), we compared the phosphorescence spectra of the TPA with three internal heavy atoms, tris(4bromophenyl)amine (TPA-3Br), at a concentration of 0.5 wt % and 12 wt % in PS at 80 K, respectively, and indeed observed a change in emission maximum from 433 to 455 nm, or 1117 cm À 1 in energy (Figure 3b).…”
Section: Resultsmentioning
confidence: 97%
“…(d) Chemical structures of P1–P6. Reproduced with permission from ref . Copyright 2022 Wiley-VCH GmbH.…”
Section: Construction Of Polymer-based Rtp Systemsmentioning
confidence: 99%
“…Zhang et al 37 synthesized a series polyester (P1−P6) through a solvent-free, ring-opening polymerization of D,L- lactide and ε-caprolactone using modified dihydroxy-functionalized naphthalenediimide (NDI) derivatives as initiators (Figure 4d). Because the NDI backbone can easily form aggregates, both monomer and aggregate RTP emissions were detected.…”
Section: Polymers Bound With Organic Luminophorementioning
confidence: 99%